Fungsi Badan Ke-Esaan Gereja dalam Memperkuat Kesatuan Iman Kristiani - Remita Nian Permata Zendrato; Meditatio Situmorang (Publisher STPKat, 2025)
This journal explores the role of the Church Unity Body in strengthening the unity of Christian faith. The Church, as the body of Christ composed of various members from diverse backgrounds and traditions, is called to unite in one faith, one teaching, and one way of life aligned with the teachings of Christ. This unity is crucial for maintaining harmony within the community of believers and for addressing social and theological challenges in the modern world.The role of the Church Unity Body is evident through Bible teaching based on enduring truth, participation in sacraments such as Holy Communion and Baptism, as well as collaboration among churches in social service and mission. In this context, the church functions not only as a place of worship but also as a community that supports spiritual growth and the well-being of its members. The unity of Christian faith requires mutual respect, forgiveness, and humility among church members. By strengthening this unity, the church can provide a clearer testimony to the world, demonstrating that in Christ, differences can be reconciled in love that transcends all. This article also highlights the importance of the church’s role in building a unity of faith that goes beyond denominational boundaries, within the framework of ecumenism, to realize the wholeness of the body of Christ and bring about transformation in the world.